2005
DOI: 10.1007/s11664-005-0041-5
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of multicolor MWIR/LWIR and LWIR/VLWIR detector arrays

Abstract: Multicolor infrared (IR) focal planes are required for high-performance sensor applications. These sensors will require multicolor focal plane arrays (FPAs) that will cover various wavelengths of interest in mid wavelength infrared/long wavelength infrared (MWIR/LWIR) and long wavelength infrared/very long wavelength infrared (LWIR/VLWIR) bands. There has been significant progress in HgCdTe detector technology for multicolor MWIR/LWIR and LWIR/VLWIR FPAs. 1-3 Two-color IR FPAs eliminate the complexity of multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Two-color MWIR/LWIR HgCdTe detectors have been examined theoretically. 38,[164][165][166] It has been shown that it is possible to predict, with relatively good accuracy, the performance of complex detectors by using numerical models. Furthermore, the simulation technique is also useful for understanding the effects of different material parameters and geometrical characteristics on the detector performance.…”
Section: A Hgcdte Dual-band Detectorsmentioning
confidence: 99%
“…Two-color MWIR/LWIR HgCdTe detectors have been examined theoretically. 38,[164][165][166] It has been shown that it is possible to predict, with relatively good accuracy, the performance of complex detectors by using numerical models. Furthermore, the simulation technique is also useful for understanding the effects of different material parameters and geometrical characteristics on the detector performance.…”
Section: A Hgcdte Dual-band Detectorsmentioning
confidence: 99%